Association between nurse aide staffing and patient mortality after major cancer surgeries in acute care settings: A retrospective cohort study. (15th February 2022) - Hirose, Naoki; Morita, Kojiro; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo
Abstract: This study examined the association between adding nurse aides and patient mortality in acute care settings. We conducted a retrospective cohort study using a national healthcare administrative claims database. We identified patients who underwent planned surgery for six types of cancer from 2010 to 2017. Multivariable logistic analyses were used to examine the association between the nurse aide staffing level and patient outcomes. The primary outcomes were failure to rescue and 30‐day hospital mortality. We examined 330 666 in‐hospital patients. The median number of nurse aides per 100 occupied beds was 6.60 (interquartile range, 4.61–8.43). In the multivariable analysis, nurse aide staffing level was not significantly associated with failure to rescue or 30‐day hospital mortality. The Japanese government provides economic incentives to hospitals that hire more nurse aides, expecting that a higher nurse aide staffing level will help licensed nurses concentrate on the tasks that need their specialties. However, our findings suggest that adding nurse aides may not be associated with lower rates of failure to rescue or 30‐day hospital mortality in acute care settings.